2014
DOI: 10.1159/000369939
|View full text |Cite
|
Sign up to set email alerts
|

Modified-Release Calcifediol Effectively Controls Secondary Hyperparathyroidism Associated with Vitamin D Insufficiency in Chronic Kidney Disease

Abstract: Background/Aims: Vitamin D insufficiency drives secondary hyperparathyroidism (SHPT) and is associated with increased cardiovascular mortality in patients with chronic kidney disease (CKD). SHPT is poorly addressed by current vitamin D repletion options. The present study evaluated a novel investigational vitamin D repletion therapy: a modified-release (MR) formulation of calcifediol designed to raise serum 25-hydroxyvitamin D in a gradual manner to minimize the induction of CYP24 and, thereby, improve the SHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 61 publications
2
49
0
Order By: Relevance
“…Data from the 3 trials presented herein, and from one previous controlled study [10] , have all demonstrated that ER calcifediol is well tolerated at higher 25-hydroxyvitamin D levels within the normal range and that subjects' compliance with the prescribed doses is excellent. The incidences of TEAEs in studies A and B were similar between subjects treated with ER calcifediol and placebo, and there was a low rate of discontinuations due to TEAEs (5.3% for ER calcifediol compared with 4.2% for placebo).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Data from the 3 trials presented herein, and from one previous controlled study [10] , have all demonstrated that ER calcifediol is well tolerated at higher 25-hydroxyvitamin D levels within the normal range and that subjects' compliance with the prescribed doses is excellent. The incidences of TEAEs in studies A and B were similar between subjects treated with ER calcifediol and placebo, and there was a low rate of discontinuations due to TEAEs (5.3% for ER calcifediol compared with 4.2% for placebo).…”
Section: Discussionmentioning
confidence: 60%
“…A single-dose comparative clinical study showed that ER calcifediol was more effective than IR calcifediol in lowering elevated plasma iPTH in CKD patients with vitamin D insufficiency [14] . A 6-week randomized, double-blind placebo-controlled study in CKD patients demonstrated that daily bedtime doses of 30, 60 or 90 μg of ER calcifediol increased serum 25-hydroxyvitamin D levels to ≥ 30 ng/ml in more than 90% of treated subjects and dosages of ≥ 60 μg/day reduced plasma iPTH by ≥ 30% from pretreatment baseline in more than 60% of subjects without meaningful impact on serum Ca, P or FGF23 [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, there are limited reports of well-designed, randomized, controlled studies of these agents, or for comparisons of the efficacy of active vitamin D or analogs, conducted in patients with CKD [10] . In one recently published (2014) trial in patients with CKD who were not undergoing dialysis, calcifediol for 6 weeks has been shown to significantly increase serum 25-hydroxyvitamin D and decrease plasma iPTH ( ≥ 30% in >60% patients treated with 60 or 90 μg/day) levels compared with placebo [22] . In pre-dialysis patients with CKD stage 3 or 4, treatment with cholecalciferol for 12 weeks has been shown to significantly increase serum vitamin D compared with placebo; however, effects on plasma PTH levels were not statistically significant (-31 vs. -7% for placebo) [23] .…”
Section: Vitamin D Replacement Therapy In Ckdmentioning
confidence: 99%